The construction, prediction and measurement of co-crystal ternary phase diagrams as a tool for solvent selection - Holaň, Jan; Stěpánek, František; Billot, Pascal; Ridvan, Luděk (European journal of pharmaceutical sciences, 2014)
Many active pharmaceutical ingredients (APIs) are poorly soluble and therefore poorly bioavailable. In recent years, the advances in crystal engineering have motivated the research in the design of pharmaceutical co-crystals. This study examines the combination of solvent selection and co-crystal ternary phase diagram prediction on the basis of solubility measurements into a single methodology that can be integrated into the pharmaceutical process development workflow. Ternary diagrams constructed from agomelatine citric acid co-crystal solubility data were compared with those obtained by modern calorimetric method called discontinuous isoperibolic thermal analysis (DITA). A suitable solvent for the co-crystallization process has been chosen on the basis of agomelatine citric acid co-crystal solubility, which is connected to the yield of the crystallization process. Furthermore, the quality of final crystals from crystallization experiments was evaluated.
Keywords: Temperature; teplota; Solubility; Calorimetry; rozpouštědla; léčivé přípravky; krystalizace; rozpustnost; kyselina citronová; kalorimetrie; Citric Acid; Solvents; Pharmaceutical Preparations; Crystallization